Longitudinal analysis of microvascular perfusion and neurodegenerative changes in early type 2 diabetic retinal disease. Issue 4 (8th December 2020) - Aschauer, Julia; Pollreisz, Andreas; Karst, Sonja; Hülsmann, Martin; Hajdu, Dorottya; Datlinger, Felix; Egner, Berit; Kriechbaum, Katharina; Pablik, Eleonore; Schmidt-Erfurth, Ursula Margarethe
Abstract : Aim: To prospectively monitor subclinical changes in capillary perfusion and retinal layer thickness in patients with type 2 diabetes and early diabetic retinal disease over 2 years. Methods: In this longitudinal study we performed biannual retinal vascular imaging using optical coherence tomography angiography (RTVue) to analyse the foveal avascular zone (FAZ) area, perimeter, acircularity index (AI) and parafoveal superficial/deep vessel density (VD). Spectral-domain optical coherence tomography (Spectralis) was used to measure the thickness of nine macular layers and the peripapillary nerve fibre layer. Results: Among 117 eyes (58 left) of 59 patients (21 female), 105 had no diabetic retinopathy (DR), 6 mild and 6 moderate non-proliferative DR at baseline. We found DR progression in 13 eyes at year 2. The FAZ area (+0.008±0.002 mm 2 /year, p<0.0001), perimeter (+0.036±0.010 mm/year, p=0.006) and AI (+0.005±0.002/year, p=0.0280) increased significantly. A pronounced decrease was found in the superficial (−1.425±0.290%/year, p<0.0001) but not the deep VD. Inner neuroretinal loss was confined to the ganglion cell (−0.539±0.150 µm/year, p=0.0004) and the inner plexiform layer (−0.361±0.127 µm/year, p=0.0045). In the outer retina, we observed a statistically significant decrease in thickness in the outer plexiform, photoreceptor layer and pigment epithelium of −0.921±0.161 µm/year, −0.325±0.139 µm/year and −0.385±0.084 µm/year, respectively. Conclusion: Subclinical signs of microangiopathy and neurodegeneration appear in parallel and are highly progressive even in the earliest stages of diabetic retinal disease. Trial registration number EudraCT20156000239634.